PELATIHAN MANAJEMEN USAHA DAN PEMASARAN DIGITAL DALAM PENGEMBANGAN USAHA FROZEN FOOD BAHAN BAKU IKAN - Tyas Permata Sari, S.Gz, M.Si; Nila Reswari Haryana; Yatty Destani Sandy; Wira Firmansyah (COVIT (Community Service of Health), 2022)
North Sumetera has a fairly high fishery yield, especially in Kecematan Percut Sei Tuan. The main commodity is mackerel. However, the results of too much mackerel have not been used well. MTS Al-Wasiyah 19 as a service partner seeks to process fishery products into frozen processed food, but in the process of marketing and management still finds many obstacles and wants to further increase income generation. The purpose of this service activity is to carry out mapping related to business management and digital marketing on processed fish products. The methods used in this service activity are dicussion, interviews, training and mentoring. The activity was held on October 18, 2021 at MTS AL Wasliyah 19 Percut Sei Tuan with the target of teachers who want to increase income generation. Activities proceed smoothly and achievement indicators can be achieved. The teachers gave a positive response by conducting questions and answers in the discussion. At the end of the meeting the teachers and the service team agreed on the name of the product to be used in marketing activities. Keywords: Business Management, Digital Marketing, Fish, Forzen Food.